Matošev loboratorij : rad, goli život i tumačenje snova - Jukić, Tatjana (Array, 2012)
My contribution is organized around a comparative analysis of Antun Gustav Matoš's „Around Lobor“ (1907), which foregrounds a peculiar configuration of dreams and Croatian cultural history, against Freud's precepts for the interpretation of dreams in Die Traumdeutung. By pointing out to overlaps in these two texts, I argue that Matoš's take on the oneiric signals the position where psychoanalysis needs to reasses its investment in dreams in terms of political economy and the management of life. Further, I argue that Freud's Die Traumdeutung provides in turn the framework whereby Matoš's account of Croatian cultural history is tooled up into a critical instrument.